Herbert Kegel: Legende ohne Tabu, ein Dirigentenleben im 20. Jahrhundert - Kuschmitz, Helga 1938- (Altenburg Kamprad, 2003)
Herbert Kegel (1920-1990), honorary conductor of the MDR Symphony Orchestra, worked for the radio in Leipzig from 1949 to 1978, initially as choirmaster, later as conductor and chief conductor of the Great Radio Orchestra, the Symphony Orchestra and the Radio Choir, after working in Pirna and Rostock. His interpretations of great choral symphonies, the masterpieces of the 20th century and his concert performances of operas are legendary. He made the Rundfunkchor one of the best and most sought-after choirs in the world. In 1977, Herbert Kegel took over as chief conductor of the Dresden Philharmonic Orchestra, a position he held until his retirement in 1985. With several tours of Japan in the 1980s, he achieved a kind of cult status there. This book reports on all these events and stages, but also on the unknown sides of Herbert Kegel's personality. In addition to numerous photos, it also contains large-format reproductions of paintings that relate to Kegel's life and illuminate his artistic facets. The author is the long-standing radio journalist and producer Helga Kuschmitz, who has organised many broadcasts and concerts with Herbert Kegel over the decades. A CD is included with the book: ‘Das klagende Lied’ by Gustav Mahler as a concert recording from the 1985 Gewandhaus Festival, “Vier Lieder für Klavier und hohe Stimme”, composed by Herbert Kegel, as well as a rehearsal recording of Gustav Mahler's 8th Symphony at the 1981 Dresden Music Festival. (Translated with Deepl.com)
Keywords: Kegel, Herbert -- 1920-1990; 20th Century (1901-2000); Music history; Conductor